THE EFFECTS OF PRANAYAMA, HATHA AND RAJA YOGA ON PHYSICAL PAIN AND THE QUALITY OF LIFE OF WOMEN WITH MULTIPLE SCLEROSIS - Doulatabad, Shahla Najafi; Nooreyan, Khirollah; Doulatabad, Ardavan Najafi; Noubandegani, Zinat Mohebbi (African Journal of Traditional, Complementary and Alternative Medicines, 2012)
In a clinical trial carried out on 60 women with multiple sclerosis, the researchers obtained data using survey questionnaires. In addition to demographic data, the Multiple Sclerosis Quality of Life-54 (MSQoL-54) instrument was used to determine how multiple sclerosis influences the quality of life of the studied women. Within the frame of this randomized controlled trial, the participants were divided into two equally sized groups (the case and the control group) in which the level of pain and the quality of life were evaluated. The case group exercised pain-managing Yoga methods for three months, keeping the pace of eight 90 minute - sessions per month. The control participants were subjected to no intervention. One month after the Yoga therapy, the level of pain and the quality of life were evaluated in both groups and compared to the baseline data. Data were analyzed using SPSS software and paired t-tests. After the Yoga therapy, the case group showed a significant improvement in physical pain management (P=0.007) and the quality of life (P=0.001) as compared to the control group. The results showed that Yoga techniques can alleviate physical pain and improve the quality of life of multiple sclerosis patients.